The intergenerational sequelae of war captivity: the impact of a self-amplifying cycle of PTSD and attachment insecurities on offspring's attachment orientations. Issue 1 (31st December 2020) - Aloni, Roy; Mikulincer, Mario; Zerach, Gadi; Solomon, Zahava
ABSTRACT: Background : War captivity is one of the most severe human-made traumatic events which lead to self-amplifying cycle of post-traumatic stress disorder (PTSD) symptoms and attachment insecurities. Solid evidence in the literature pointed out on the intergenerational transmission of PTSD symptoms. However, no research has been conducted on the intergenerational transmission of attachment insecurities and the effect of the self-amplifying cycle among former prisoners of war (ex-POWs) and their offspring attachment insecurities. Objective : This research aims to explore the intergenerational impact of a self-amplifying cycle of PTSD and attachment insecurities among ex-POWs on their offspring's attachment orientations. Method : We sampled dyads of Israeli ex-POWs of the Yom Kippur war and their adult offspring (ex-POW group) ( n  = 80) as well as dyads of Israeli veterans who fought in the Yom Kippur war, but were never held captive, and their adult offspring (control group) ( n  = 40). Veterans reported on PTSD severity and attachment orientations (anxiety, avoidance). Offspring reported on attachment orientations. We conducted (a) hierarchical regressions to predict offspring attachment orientations as a function of veterans' attachment orientations, and (b) moderated mediation analyses examining the role of veterans' PTSD in the intergenerational transmission of attachment orientations. Results : Ex-POWs' attachment anxiety was associated with offspring's reports of higher attachment anxiety and avoidance, and this intergenerational transmission of attachment was mediated by ex-POWs' PTSD severity. These effects were not significant in the control group. Conclusions : Decades after the war end, the intergenerational sequelae of war captivity are evident by the impact of the self-amplifying cycle of PTSD and attachment insecurities among ex-POWs and their offspring's attachment insecurities. Therefore, it is imperative for clinicians to recognize the intergenerational transmission and to focus not only on the trauma but also on the traumatized person's attachment injuries and the shattering of core beliefs about the world, self, and others, in the context of attachment-based therapies. Abstract : HIGHLIGHTS: War captivity is a potent pathogen for Posttraumatic Stress Disorder (PTSD) symptoms and attachment injuries apart and simultaneously. Studies revealed the self-amplifying cycle of PTSD symptoms and attachment insecurities decades after the captivity trauma ended. Solid evidence in the literature pointed out on the intergenerational transmission of PTSD symptoms. However, no research has been conducted on the intergenerational transmission of attachment insecurities and the effect of the self-amplifying cycle among former prisoners of war (ex-POWs) and their offspring. Ex-POWs' attachment anxiety was associated with offspring's reports of higher attachment anxiety and avoidance, and this intergenerational transmission of attachment was mediated by ex-POWs' PTSD severity. Therefore, it is imperative for clinicians to recognize the intergenerational transmission and to focus not only on the trauma but also on the traumatized person's attachment injuries and the shattering of core beliefs about the world, self, and others, in the context of attachment-based therapies.